A case of Actinomycotic mycetoma involving the right foot - Ragini Tilak; Sanjay Singh; Atul Garg; Jaya Bassi; Vijai Tilak; Anil K. Gulati (Journal of Infection in Developing Countries)
A 45-year-old male presented with history of multiple swellings over the foot with sinuses discharging seropurulent pus. Actinomadura madurae was demonstrated and identified by microbiological culture from the pus obtained directly of the lesion. This case is reported to emphasize the importance of laboratory diagnosis in the management and assessment of the prognosis of such cases.